DECENTERING STRUGGLE: TRAUMATIZING CENTRAL AMERICANS - Rønsbo, Henrik (Psyke & Logos, 2004)
This essay demonstrates the ways in which Central American subjects during the last three decades have been centered by changing discourses on violence. From violence entextualized as intrinsic to the eschatological history of the people, to the violence as an autonomous process, that creates entire populations of traumatized. Within this entextualizing trauma is seen as the normal reaction to violence and the ability of social groups and individuals to act has been silenced while agency is transferred to the entities of psycho-social support: The psycho-social interventions combine individualizing and totalizing techniques through which entire populations are placed at the margins of society, living lives in which their emotional state is monitored by humanitarian agencies and interventions designed according to registered levels of well-being and the prevalence of psychological trauma in the general population. By entextualizing violence as an autonomous process, which generates trauma that trough feed-back effects may reproduce themselves over several generations, we have arrived at a theoretical model of life at the margins, which is ill equipped to explain the ways in which violence, everyday life and the exercise of power are articulated in post-colonial societies in Latin America, Africa and Asia.